EXPLORING THE ASSOCIATION BETWEEN EXTRA-CARDIAC TROPONIN ELEVATIONS AND RISK OF FUTURE MORTALITY - Lippi, Giuseppe; Sanchis-Gomar, Fabian (Journal of Medical Biochemistry, 2020)
Although the measurement of cardiac troponin I (cTnI) and T (cTnT) has now become the cornerstone for diagnosing cardiac injury, both ischemic and non-ischemic, recent evidence has become available that many patients display extra-cardiac causes of cTn elevations and carry a considerably enhanced risk of future mortality. The current literature data suggests that cTn elevations may be equally common in patients with cardiac and extra-cardiac diseases. Among the latter cohort of patients, the leading extra-cardiac diseases which may be responsible for either cTnI or cTnT elevations include infectious diseases/sepsis, pulmonary disorders, renal failure, malignancy, as well as gastrointestinal, neurological and musculoskeletal diseases. What also emerges rather clearly from the current literature data, is that the risk of dying for extra-cardiac diseases is higher (i.e., between two- to three-fold) in patients with extra-cardiac cTn elevations than in those with cardiac pathologies, and that the most frequent cause of death would then be infections/sepsis, followed by malignancy, respiratory disorders, myocardial infarction, gastrointestinal and neurological diseases, heart failure, stroke, cardiac arrhythmias, renal failure, psychiatric, metabolic, urogenital and musculoskeletal disorders. These figures would lead to conclude that there is a considerable risk that the underlying pathology causing cardiac injury and cTn elevation would then become the cause of death in these patients. This important evidence shall lead the way to defining appropriate and effective strategies for managing patients with extra-cardiac cTn elevations, so that their risk of future death could be prevented or limited.
Keywords: mortality, myocardial infarction, cardiac injury, troponin